The pancreas. Issue 10 (October 2017) - Cade, Jennifer E.; Hanison, James
Abstract: The pancreas plays a vital role in coordinating and regulating digestion and nutrient metabolism, and does so via endocrine and exocrine processes. Insulin and glucagon are produced within the endocrine pancreas to not only achieve glucose homeostasis, but regulate protein and fat metabolism. Enzymes and zymogens are secreted in alkaline pancreatic fluid to aid digestive function. This article looks at how the pancreas achieves such precise synthetic and secretory functions, and reviews the physiology of the secreted hormones and enzymes.